2018
DOI: 10.1021/acs.biochem.8b01004
|View full text |Cite
|
Sign up to set email alerts
|

A Biophysical Perspective on Enzyme Catalysis

Abstract: Even after a century of investigations, our knowledge of how enzymes work remains far from complete. In particular, several factors that enable enzymes to achieve the high catalytic efficiency still remain only poorly understood. A number of theories have been developed, which propose or reaffirm that enzymes work as structural scaffolds, serving to bringing together and properly orienting the participants so that the reaction can proceed; therefore, only viewing enzymes as passive participants in the catalyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
140
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(141 citation statements)
references
References 117 publications
(317 reference statements)
0
140
0
1
Order By: Relevance
“…In these cases the results of biophysical studies on protein dynamics may not be relevant to the explanation for the enzymatic rate acceleration. 111 Now the only protein motions clearly relevant to the rate acceleration are those associated with the creation and breakdown of E C ·S during the steps for k c , k –c , and k ′ –c in Scheme 7 . These motions may affect the reaction rate, if they occur together with conversion of enzyme-bound substrate to product in a single reaction stage.…”
Section: Effect Of Protein Motions On Enzyme Turnovermentioning
confidence: 99%
“…In these cases the results of biophysical studies on protein dynamics may not be relevant to the explanation for the enzymatic rate acceleration. 111 Now the only protein motions clearly relevant to the rate acceleration are those associated with the creation and breakdown of E C ·S during the steps for k c , k –c , and k ′ –c in Scheme 7 . These motions may affect the reaction rate, if they occur together with conversion of enzyme-bound substrate to product in a single reaction stage.…”
Section: Effect Of Protein Motions On Enzyme Turnovermentioning
confidence: 99%
“…For example, enzymes commonly contain loops that close to interact with substrates, and emerging results provide evidence that the most reactive sub-states in enzymatic reactions are not the most populated (Callender and Dyer, 2015;Klinman, 2009Klinman, , 2013Reddish et al, 2014). It has been also suggested that the ability to adopt reactive conformations may be dynamically linked to surface residues and solvent (Agarwal, 2004(Agarwal, , 2019Agarwal et al, 2002Agarwal et al, , 2004Meadows et al, 2014;Ramanathan and Agarwal, 2011) and further proposed that catalytic rates are gated by collective dynamic events of the protein (Silva et al, 2011;Suarez and Schramm, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…For several decades, the pioneering work of Frauenfelder and coworkers indicated that hydration shell solvent motions have a direct and strong influence on internal protein residue motions . Driven by the temperature‐associated fluctuations, the motions of solvent molecules at surface enslave the motions of protein surface residues, which in turn influences how the longer time‐scale motion sampling occurs …”
Section: Cellular Environment and Solvent Effects On Functional Enzymmentioning
confidence: 99%
“…Another excellent article by Schwartz builds a consensus view emerging from experimental and computational techniques, particularly on the role of fast motions in enzyme reactions . Agarwal also summarized a biophysical model of enzymes based on enzyme and solvent dynamics with focus on pathways of energy transfer between the dynamical surface loop regions and the active‐site of several enzymes …”
Section: Introductionmentioning
confidence: 99%